2020
DOI: 10.1111/gcbb.12679
|View full text |Cite
|
Sign up to set email alerts
|

Cut‐and‐chip harvester material capacity and fuel performance on commercial‐scale willow fields for varying ground and crop conditions

Abstract: Shrub willow (Salix spp.) is capable of producing commercially attractive amounts of biomass in short rotations, but harvesting costs and logistics remain a concern.There is a particular need for information about harvesting operations on larger, commercial short-rotation woody crop systems. Another recent issue on commercial fields in northern New York is commercial growers conducting harvests during the growing season rather than the recommended dormant season when fields may be too wet to harvest. This stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…Harvesting accounts for 9.48 kg CO 2eq Mg −1 in all scenarios and is the second largest impact among crop management activities after fertilizer, so improvements in harvester efficiency can contribute to GHG emission reductions. This number is about 27% lower than the 13 kg CO 2eq Mg −1 value in a previous study [1] due to improvements in harvester efficiency of single pass cut and chip operations modeled in this study and improved data for harvester operation and fuel consumption that have been made over the past few years [29,46]. Site management is an integrated category including all site preparation, planting, and site maintenance processes, specifically including processes #1 to # 15 and process #20 in Table S1.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Harvesting accounts for 9.48 kg CO 2eq Mg −1 in all scenarios and is the second largest impact among crop management activities after fertilizer, so improvements in harvester efficiency can contribute to GHG emission reductions. This number is about 27% lower than the 13 kg CO 2eq Mg −1 value in a previous study [1] due to improvements in harvester efficiency of single pass cut and chip operations modeled in this study and improved data for harvester operation and fuel consumption that have been made over the past few years [29,46]. Site management is an integrated category including all site preparation, planting, and site maintenance processes, specifically including processes #1 to # 15 and process #20 in Table S1.…”
Section: Discussionmentioning
confidence: 58%
“…As a result, the range of EROI values in this study (8. [9]. Harvesting throughput values in our study are based on more recent data that showed a substantial improvement in harvester throughput [29,46] that results in lower energy consumption per Mg of biomass and a higher EROI. Further improvements in harvesting and chip loading operations may be possible to further lower energy inputs into the system.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, commercial harvests have not necessarily occurred within the recommended window; site conditions, especially on poorly drained marginal land in the northeast U.S., may limit machine access and operators may elect to expand the harvesting window [24]. The timing of willow harvests can potentially impact coppice regeneration and regrowth, and ultimately impact the productivity and costs [19].…”
Section: Introductionmentioning
confidence: 99%
“…The search for crops that would meet the criteria of sustainable development and make good raw material for bioenergy and bioeconomy has been the subject of numerous papers [34][35][36], many of which determined specific conditions for their cultivation [37], harvest [38][39][40][41][42][43][44][45][46][47], and factors affecting the crop per area unit [48] and the impact of cultivation on greenhouse gases (CHG) [49,50] and on the environment [51][52][53]. Mathematical methods were used by Bender et al [54], Hauk et al [55], Salles et al [56], and Sleight et al [57,58] to assess crop yields; by Havlíčková et al [59] to assess the SRC biomass price; and by Frank et al [60] to assess both the minimum selling price and net present value (NPV).…”
Section: Introductionmentioning
confidence: 99%